CT-04 Safety and efficacy of allogeneic umbilical cord-derived mesenchymal stem cells (MSCs) in patients with systemic lupus erythematosus: results of an open-label phase I study. (August 2018) - Kamen, Diane L; Nietert, Paul J; Wang, Hongjun; Duke, Tara; Cloud, Colleen; Robinson, Angela; Gilkeson, Gary S
Abstract : Background: Mesenchymal stem cells (MSCs) are known to possess significant immunosuppressive properties, and their use in refractory SLE is supported by promising safety and efficacy in autoimmune animal models and human trials. We conducted this phase I open-label study to test the hypothesis that a single infusion of human allogeneic umbilical cord-derived MSCs (IND 16377) is safe when added to standard-of-care therapy for active SLE. The primary safety outcome is frequency of Grade 3 or higher adverse events (AEs) by Week 24. The primary efficacy outcome is change in SLE disease activity between Baseline and Week 24 measured by SLEDAI score and prednisone dose. Methods: Patients (n=6) with active SLE (SLEDAI ≥6) who signed informed consent and met all inclusion and exclusion criteria sequentially received 1 × 10 6 cells/kg umbilical cord-derived MSCs given as an IV infusion in Plasma-Lyte A solution. Post-infusion, Week 1 and 2 safety data from each participant was reviewed by the Data Safety Monitoring Board prior to enrolling the next patient. Primary safety and efficacy endpoints were determined at Week 24. Each patient is followed for a total of 52 weeks. Results: Table 1 summarizes the demographics, visit SLEDAI scores, number of serious and non-serious adverse events (SAEs, AEs). The 6th participant completed their Week 24 visit on April 11, 2018. To date, there has been 1 SAE, deemed not unexpected and not attributed to investigational product. No non-serious AEs higher than Grade 2 by NCI-CTCAE scoring were reported. The SAE was prolonged hospitalization following a partial dose infusion of rituximab IV leading to anaphylaxis. Rituximab was started for persistent SLE disease activity (patient dropped out of the study after Week 8) and was given in the hospital ICU setting due to her prior history of anaphylaxis to Tween (polyethoxylated surfactant found in IV and SQ medications). Anaphylaxis resulted in a prolonged hospital stay of 2 days, resolving with treatment without sequelae. The SAE was attributed to her known allergy to ingredients in the rituximab infusion and deemed unrelated to the MSCs that she received several months earlier. The AEs 'possibly' attributable to the investigational product were Grade 2 nausea, Grade 2 tachycardia, and Grade 1 flushing with Grade 1 toe paresthesias – all of which resolved without sequelae. Among the 5 patients who completed their Week 24 evaluations, all showed improved SLE activity (mean SLEDAI score 8.6±1.9 at Baseline improved to 2.6±2.8 at Week 24) with stable or lower doses of prednisone and stable background immunosuppressants. Mean physician global assessment (PGA) scores also improved from 1.71±0.48 at Baseline to 0.32±0.17 at Week 24. Conclusions: A single-dose of umbilical cord-derived MSCs was safe and well-tolerated in this open-label phase I trial for 6 patients with active SLE. Initial efficacy data for MSCs in SLE appears promising and will be further tested in a larger controlled trial. Acknowledgements: We would like to thank all of the study participants for their time and commitment to the study. This research study was supported by grants from the Lupus Foundation of America and the National Institutes of Health: National Institute of Allergy and Infectious Diseases (R34 AI114453) and the South Carolina Clinical and Translational Research (SCTR) Institute at the Medical University of South Carolina (UL1 RR029881). Trial registration: NCT 03171194